HIV/AIDS in the Caribbean : Issues and Options - World Bank (Washington, DC, 2013)
Intensified efforts are needed in the Caribbean region if inroads are to be made against the AIDS epidemic. Although many Caribbean governments have initiated a limited response to HIV/AIDS, much remains to be done to bring proven interventions quickly up to nationwide scale. Moreover there is growing recognition that HIV/AIDS is not just a serious health issue in developing countries, but a major developmental catastrophe that threatens to dismantle the social and economic achievements of the past half century. The challenge for Caribbean countries is to learn from the dramatic experiences of some African countries and act decisively now to prevent the progressive extension of the epidemic to the general population. This report provides an overview of the challenges and opportunities in addressing the problem of HIV/AIDS in the Caribbean. It presents a snapshot of the HIV/AIDS epidemic in the region, offers examples of ways in which Caribbean countries and regional bodies have responded to the epidemic, discusses alternative actions for addressing the crisis, and highlights a range of strategies for donor coordination and cooperation in the region. Finally, the report identifies the potential role of the World Bank in addressing the HIV/AIDS epidemic in the Caribbean.